Optimization of provision of specialized medical care for patients with maxillofacial neoplasms in the Penza region of Russia - M. V. Lebedev; K. I. Kerimova (Biomedical Photonics, 2021)
Recent years are characterized by the active development and advancement in clinical practice of the method of photodynamic therapy (PDT). PDT shows high effectiveness in the treatment of skin tumors, digestive, nervous, respiratory systems, in gynecology, ophthalmology. Antimicrobial PDT is successfully used in the treatment of purulent wounds and infectious diseases. One of the most actively developing applications of antitumor PDT is the treatment of maxillofacial tumors.The study assessed the organization of medical care for patients with malignancies of the maxillofacial region (MNMR) in the Penza region and the provision of oncologists, maxillofacial surgeons specializing in the treatment of tumor pathology. In the course of the study, the incidence of MNMR of the population of the Penza region and the gender and age structure were determined. The shortcomings of the organization of medical care for patients with MNMR are indicated.